Refining Spectrum Fee to Increase Utilization Efficiency by Adopting ITU-R SM 2012-2 Case Study: Cellular Service in Indonesia - Ismail Ismail; Suhono H. Supangkat; Hendrawan Hendrawan; Basuki Y. Iskandar (LPPM ITB, 2010)
The spectrum fees called as